Effect of semi-circular wavy liner on performance of journal bearing - Md. Sheriff, Jamaluddin (2012)
The amount of lubricant present in a bearing can affect its performance. This study compares the load carrying capacity of wavy and smooth surfaces liner bearing so that the potential advantages of the former could be identified. Both types of bearing used palm oil as lubricant and computational analysis was developed to predict the numerical data for full film lubrication condition. The bearing model was 60 mm in diameter and its ratio of length to diameter was 0.5 with clearance and amplitude of 250μm and 200μm respectively. All cases studied included temperature effect under steady flow conditions with speed between 200 and 5000 rpm. The results show, for low eccentricity ratio, semi circular wavy liner bearings were able to produce higher load carrying capacity. The results also show that the overall temperature drop for wavy liner surfaces was higher for all test conditions. The shaft speeds, however, have no direct effect on the magnitude of the load carrying capacity.